Performance of constructed wetlands in the treatment of aerated coffee processing wastewater: Removal of nutrients and phenolic compounds - Rossmann, Maike; Matos, Antonio Teixeira de; Abreu, Edgar Carneiro; Silva, Fabyano Fonseca e; Borges, Alisson Carraro (Ecological Engineering, 2012)
Given the scarcity of studies on the behavior of constructed wetlands (CWs) when operating with previously aerated wastewater, the objective of the present study was to evaluate the influence of artificial aeration and vegetation on removal of nutrients and phenolic compounds from coffee processing wastewater (CPW) treated in CWs cultivated with ryegrass (Lolium multiflorum Lam.) For this reason, CWs were constructed measuring 0.6 m × 0.5 m × 2.0 m (H × L × W) and filled with pea gravel to a height of 0.55 m. The experiment was carried out considering a completely randomized design (CRD). Each variant of the experiment was replicated 10 times for each one of two replicates, implying in a total of 20 replicates, and 4 CWs characterized as follows: (i) ryegrass cultivated systems operating with an aerated influent (aiCWc), (ii) non-cultivated systems operating with an aerated influent (aiCW*), (iii) ryegrass cultivated system operating with a non-aerated influent (CWc), and (iv) non-cultivated systems operating with a non-aerated influent (CW*). For oxygenation of the CPW which would be supplied as aerated CPW in two treatments, an aeration system was implanted in the storage tank, consisting of a submerged Sarlobetter S520 pump with a flow of 0.52 m^3 h^−1, a gravel filter and tulle. The CPW was applied at an average flow rate of 0.020 m^3 d^−1, corresponding to a hydraulic retention time of 12 days. Efficiencies of 69, 72, 30 and 72% were obtained for the removal of total nitrogen (NT), total phosphorus (PT), total potassium (KT) and total phenolic compounds (FT), respectively, in the aiCWc. Aeration resulted in improved efficiency of pollutant removal such as N, P and phenolic compounds. The cultivated plant species (L. multiflorum) influenced the removal efficiencies of total-N, total-P and total-K in the systems, however, the best results were obtained by means of combination of vegetation with artificial aeration. Artificial aeration does not totally compensate the absence of plants, suggesting that the role of plants goes beyond the addition of oxygen to the medium, permitting the development of a more active and diverse microbial community near the root zone.
Keywords: Treatment wetland; Horizontal flow; Agro-industrial effluent; Coffee; Aeration